(untitled) (Journal of Engineering, 2020)
The reduction in the rivers capacity is one the most important issue to give the decision maker an idea during the flood season. The study area included the rivers of the Al Atshan, Al Sabeel and Euphrates, which are surveyed with a length of 21, 5 and 20 km respectively. The Euphrates , the Atshan and Al Sabeel rivers were simulated by using HEC-RAS 5.0.3 software to study the real condition within the city of Assamawa. As well as the simulation was implemented by modifying the cross sections of the Euphrates and Al Sabeel rivers to increase their capacity to 1300 and 1200 m3/s respectively which are a flood discharges100 year return periods. The results showed that the maximum discharge capacity under real conditions of Euphrates River is 750 m³/s and both Al Atshan and Al Sabeel arms are 500 m3/s.